Hubungan Peran Kader Posyandu dengan Pencegahan Terjadinya Kasus Stunting pada Ibu Yang Mempunyai Anak Balita - Lili suryani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
According to the World Health Organization (WHO), in 2022 there will be 148.1 million children under the age of 5 who are too short compared to their age (stunting), 45.0 million children who are too thin compared to their height (wasting), and 37.0 million children too heavy for his height (overweight). This research aims to determine the relationship between the role of Posyandu cadres and the prevention of stunting cases among mothers of toddlers in the Gedang Village Community Health Center Work Area in 2024. This type of research is quantitative and analytical with a cross-sectional study approach. The sampling technique used in this research was the Accidental Sampling technique. The population in this study was all Posyandu cadres in the Gedang Village Health Center Work Area, totaling 42 people with a sample of 42 people. The location of this research was carried out in the Gedang Village Community Health Center Work Area and was carried out in January-July 2024. The results showed that more than half of 24 (57.1%) of the respondents had a poor role as Posyandu Cadres and more than half of 30 (71.4%) respondents with poor prevention of stunting cases in mothers who have children under five with statistical test results (Chi-Square) obtained p-value 0.003. The research conclusion shows that there is a relationship between the role of Posyandu cadres and the prevention of stunting cases in mothers who have children under five. The researchers' suggestions from the research results can be applied in daily nursing practice, such as providing health education regarding the prevention of stunting in mothers who have children under five. As a reference for the Gedang Village Community Health Center in conducting a review of the role of posyandu cadres in preventing stunting cases by always providing health education to mothers